Indlejret Visdom – En Netværksanalyse af De Økonomiske Vismænd - Henriksen, Lasse Folke; Stahl, Rune Møller (Politik, 2014)
Approaches to the connection between economic science and politics that is based on institutional theory or Actor-network theory, stress the importance of economic ideas and scienti c models and instruments on the substantive content of policy processes. In contrast this article argues for the importance of analyzing the way economic scienti c experts are embedded in broader social structures and institutions, through the application of network-analytical methods. e article presents an analysis of the Economic Council, where a range of quantitative tools is employed to describe the positions and divergent roles of the members in the broader economic policy networks in Denmark.